Fucoidan from Fucus vesiculosus alleviates MetALD via promoting HIF-1α ubiquitination to suppress peripheral monocyte infiltration - Li, Lei; Luo, Jialiang; Wang, Di; Chang, Yuan; Duan, Chaohui; Zuo, Daming (Frontiers in Pharmacology, 2025)
Metabolic and alcohol-related liver disease (MetALD), characterized by excessive alcohol intake in individuals with metabolic dysfunction, is a growing health burden worldwide. Hepatic macrophages play a pivotal role in MetALD pathogenesis, with pro-inflammatory infiltrating monocytes/macrophages contributing to liver injury. Fucoidan, a sulfated polysaccharide derived from brown algae, is known for its anti-inflammatory properties, yet its intracellular targets remain poorly defined. Here, we identify prolyl hydroxylase domain-containing protein 2 (PHD2) as a novel intracellular binding partner of fucoidan. Using a high-fat diet plus ethanol-induced MetALD mouse model, we demonstrate that fucoidan significantly attenuates hepatocyte injury, steatosis, and peripheral monocyte infiltration in a dose-dependent manner. In vitro, fucoidan markedly suppressed ethanol- and LPS-induced THP-1 monocyte migration. Mechanistically, we show that fucoidan binds directly to PHD2, enhancing proteasome-mediated ubiquitination and degradation of HIF-1α, a key transcription factor driving monocyte recruitment and inflammation. Our findings reveal a previously unrecognized mechanism by which fucoidan exerts its anti-inflammatory effects via targeting the PHD2–HIF-1α axis, offering a promising therapeutic strategy for MetALD.